An investigation into the geographical trends in the sectoral composition of the Cape Town economy - Azwihangwisi, Netshikulwe (Department of Sociology, 2014)
The purpose of this research is to examine the geographical trends in the sectoral composition of the city of Cape Town economy between the year 2000 and 2005. The research is informed by related studies and theories that argued Cape Town is developing a post-Fordist spatial order characterised by the development of edge cities and the excluded ghetto. It investigates the extent to which the service sector or producer service is becoming decentralised, and the growth it had experienced compared to the manufacturing sector. We have used sectoral composition data by areas to determine the locations of the service and manufacturing sector, and undoubtedly to test this theory. To achieve our research purpose, data on actual locations of the manufacturing and service companies have been used to determine growth. The spatial trends under debate include 'edge cities' or suburbanisation, the 'excluded ghetto' and 'spatial mismatch'. The implications of the service sector growth in selected geographies are central to the study. Our findings confirmed the growth of the service sector and low decline in the manufacturing sector in the City of Cape Town. Furthermore, the data also show that the immeasurable growth of the service sector has been occurring in the northern and southern suburbs while south-east area has experienced little or no growth. Additionally, it has been observed that although the Cape Town Central Business District (CBD) has experienced a growth in the service sector, it is relatively low compared to the northern and southern suburbs areas. However, the CBD also experienced a slight decline in manufacturing which demonstrate the importance role of this sector in the area. Spatially, the evidence confirmed that it is the services sector situated to the north and south of the CBD that are experiencing increases while the south-east experienced a little growth. The implications of the growth of the service sector in the northern and southern side of the CBD is that of increased spatial and social polarisation as the job market particularly for the working class who are located further away in the impoverished south-east. These spatial trends negatively affect those living in the townships from the rest of society, particularly the working class.